From Structure to Therapy: A Comprehensive Review on the Pharmacological Applications of Tertiary Amides - Wiame Boumzour; Mohamed Merouane El Hammoumi; Mohamed Dakir; Oussama Maazouz; Mounir Belbahloul; Abdelhadi El Bachiri (Mini-Reviews in Organic Chemistry, 2026)
Tertiary amides have attracted increasing interest from pharmaceutical researchers because of their particular structural characteristics, high chemical stability, and wide variety of biological activities. Tertiary amides are present in many bioactive molecules and represent an important motif for new drug development. This review systematically discusses recent advances in the therapeutic uses of tertiary amide derivatives. Recent studies indicate that tertiary amides have great potential as anticancer agents with proven activity against gastric cancer, via the modulation of NEDDylation pathways and inhibition of cyclin-dependent kinases, leading to disruption of cancer cell proliferation and survival. Furthermore, current research shows that tertiary amide derivatives are potent against several viruses, such as the hepatitis C virus, bovine viral diarrhea virus (BVDV), dengue virus, and Tacaribe virus. These findings indicate that tertiary amide derivatives serve as effective and versatile antiviral agents for preventing and treating numerous emerging and persistent viral infections. Additionally, many tertiary amides exhibit strong activity against various pathogenic bacteria, underscoring their importance in the global effort to combat antimicrobial resistance. Several physicochemical factors that determine tertiary amides in drug discovery programs include lipophilicity, conformational rigidity, and metabolic stability; all these physicochemical parameters improve bioavailability and 'drug-like' characteristics, making these compounds ideal candidates for optimization in drug discovery programs. Overall, current evidence demonstrates the broad applicability of tertiary amides and their potential for new drug development. This review provides insights into the design and development of therapeutic agents based on tertiary amide scaffolds.